Emergency surgical obstetrics simulation training: an ex vivo low-cost model using bovine uterus and porcine bladder for haemostatic uterine brace suture techniques. (22nd April 2020) - Sinclair, Amy; Allam, Mohamed Sayed; Ferguson, Evelyn Jean; Mehasseb, Mohamed Khairy
Abstract : Postpartum haemorrhage remains a leading cause of maternal mortality and morbidity. While conventional obstetrics training curricula describe at length the management of postpartum haemorrhage, obstetrics trainees rarely have exposure to surgical management of postpartum haemorrhage in emergency situations due to reduced hours of training. Procedures such as the transverse or longitudinal haemostatic uterine brace sutures are recognised to be safe, simple and allow for the preservation of the uterus. Training during emergency situations is rarely practical or ideal. We describe a simple model that simulates the atonic postnatal uterus and allows trainees to practise the safe placement of the brace sutures. We use a bovine uterus model with attached broad ligament, bladder and ureters for the transverse haemostatic suture. For the longitudinal brace suture, we use a porcine bladder to simulate the uterus, with the ureters and bladder mesentery simulating the tubes and broad ligaments. The placement of the sutures can be practised with the uterus/bladder closed, or open akin to a caesarean section. Tissue dissection and feedback is almost similar to in vivo conditions. The sutures are inserted and driven using the material and correct placement used during real surgery. Our wet lab training model allows the acquisition, maintenance and enhancement of the required technical skills in a controlled environment, using inexpensive, reproducible and widely available specimens. The model has proved successful in both high and low-resource healthcare settings.